Socioeconomic inequalities in early initiation and exclusive breastfeeding practices in Bangladesh: findings from the 2018 demographic and health survey - Michael Ekholuenetale; Sabuj Kanti Mistry; Ritesh Chimoriya; Simone Nash; Ashish M. Doyizode; Amit Arora (BMC, 2021)
Abstract Background Optimal breastfeeding practices including early initiation of breastfeeding and exclusive breastfeeding (EBF) are associated with positive health outcomes. Socioeconomic inequalities in key breastfeeding indicators may play a role in the prevalence of breastfeeding practices. The objective of this study was to examine the socioeconomic inequalities in early initiation of breastfeeding and EBF practices in Bangladesh based on the 2018 Bangladesh Demographic and Health Survey (BDHS). Methods This was a secondary data analysis of the nationally representative 2018 BDHS. Data on 4950 women of reproductive age who had ever given birth and 924 children aged 0-5 months were extracted, for early initiation of breastfeeding and EBF. Early initiation of breastfeeding was determined from children who were put to the breast within the first hour of birth. Exclusive breastfeeding was estimated from children aged 0-5 months who were exclusively breastfed. Results The weighted prevalence of early initiation of breastfeeding and EBF were 60.8% (95% CI; 59.0, 62.6%) and 66.8% (95% CI; 63.1, 70.3%), respectively. The estimated prevalence of early initiation among the poorest, poorer, middle, richer and richest households were 67.8, 66.3, 58.4, 56.3 and 54.4%, respectively. Similarly, early initiation prevalence of 64.4, 65.0, 61.1 and 52.3% were estimated among women with no formal education, primary, secondary and higher education, respectively. The estimated prevalence of EBF among the poorest, poorer, middle, richer and richest households were 63.0, 65.2, 67.7, 66.7 and 69.9%, respectively. Similarly, the estimated EBF prevalence were 62.5, 66.0, 66.3 and 68.9% among women with no formal education, primary, secondary and higher education, respectively. Early initiation of breastfeeding was higher among lower household wealth (Conc. Index = − 0.049; SE = 0.006) and lower educational attainment groups (Conc. Index = − 0.035; SE = 0.006). Conclusions Improving optimal breastfeeding practices in Bangladesh should be given utmost priority. A need to address the socioeconomic inequalities in breastfeeding practices was also identified.